Anatomic variability of branches of iliac and femoral arteries in human fetuses - Tatiana V. KHMARA; Pavlina V. HRYHORIEVA; Alla V. VASYLCHYSHYNA; Alexander V. TSYHYKALO; Igor I. ZAMORSKII1; Mariana A. RYZNYCHUK (Archives of the Balkan Medical Union, 2019)
Introduction. The anatomy of the gluteal and anterior femoral regions is characterized by considerable age and individual variability of the muscles and neurovascular formations, which is a rather common cause of complications during surgical interventions.